A Pilot Study: The Effect of Bio-Energy on Stress for University Faculty, Staff, and Students During Finals Week. (March 2017) - Running, Alice; Hildreth, Laura
Aim: To examine the effectiveness of a bio-energy intervention on self-reported stress for a convenience sample of University students, faculty, and staff during finals week. We hypothesized that participants would report a decrease in stress after a 20 minute bio-energy intervention.Study Design: A quasi-experimental, single-group, pretest–posttest design was used.Method: Thirty-nine faculty, staff, and students participated. Participants served as their own controls. A specific technique was provided by each bio-energy practitioner for 20 minutes after participants had completed a visual analogue scale identifying level of stress and listing two positive and negative behaviors they were currently using in response to stress.Results: A one-sample t test indicates that bio-energy therapy significantly reduces stress, t (35) = 7.74, p < .0001. A multiple regression analysis further indicates that the decrease in stress levels is significantly greater for higher initial stress levels, t (31) = 4.748, p < .0001); decreases in stress are significantly greater for faculty and staff compared to students, t (31) = −2.223, p = .034; and decreases in stress levels are marginally significantly higher for older participants, t (31) =1.946, p = .061.Conclusion: Bio-energy therapy may have benefit in reducing stress for faculty, staff, and students during final examination week. Further research is needed.